The Fly Swatter Game to Enrich Students’ Vocabulary - Erlidawati (Medan Resource Center, 2022)
Learning vocabulary is one of the most important thing in learning English. Most of students still get the difficulties in learning vocabulary. They felt hard in memorizing vocabulary and they felt bored when learning vocabulary. The objective is to increase the learners’ vocabulary in mastering English language. Fly swatter game is one of the game that can use in learning English and can make the students creative and active in getting the new vocabulary by teacher instruction. Therefore, the students can implement the words that they have gotten in their speaking, writing, reading and listening. They can express their own idea when they want to speak with other, they can write their idea in writing, they can understand the meaning from the text and they can listen the speakers say something. Keywords: Fly Swatter Game, Enrich, Students’ vocabulary